The impact of visual information in speech perception for individuals with hearing loss: a mini review - Choi, Ahyeon; Kim, Hayoon; Jo, Mina; Kim, Subeen; Joung, Haesun; Choi, Inyong; Lee, Kyogu (Frontiers in Psychology, 2024)
This review examines how visual information enhances speech perception in individuals with hearing loss, focusing on the impact of age, linguistic stimuli, and specific hearing loss factors on the effectiveness of audiovisual (AV) integration. While existing studies offer varied and sometimes conflicting findings regarding the use of visual cues, our analysis shows that these key factors can distinctly shape AV speech perception outcomes. For instance, younger individuals and those who receive early intervention tend to benefit more from visual cues, particularly when linguistic complexity is lower. Additionally, languages with dense phoneme spaces demonstrate a higher dependency on visual information, underscoring the importance of tailoring rehabilitation strategies to specific linguistic contexts. By considering these influences, we highlight areas where understanding is still developing and suggest how personalized rehabilitation strategies and supportive systems could be tailored to better meet individual needs. Furthermore, this review brings attention to important aspects that warrant further investigation, aiming to refine theoretical models and contribute to more effective, customized approaches to hearing rehabilitation.